Legal Certainty in the Decisions of the Honorary Council of the Constitutional Court: A Case Study of Chairman Anwar Usman's Ruling - Totok Yanuarto; Pika Sari; Bayu Dwi Anggono; Fanny Tanuwijaya (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
The existence of the Constitutional Court in the life of the nation and state is in order to guarantee and prove the existence of positive law, especially laws, so that these laws remain in accordance with the constitution so that later the constitutional rights of citizens can be maintained. The purpose of this research is as evaluation material and learning material for law enforcers, students and other parties. This type of research is included in the juridical-normative category, namely research carried out by examining theories, concepts, legal principles and regulations that are appropriate and related to the object of research. The Constitutional Court decision that has been issued against Anwar Usman cannot be challenged in the State Administrative Court because the Constitutional Court's decision is not a state administrative decision so it does not fall within the scope of what can be litigated in the state administrative court. Another reason that could be the basis for approval or inaccuracy of the State Administrative Court's lawsuit in relation to the Constitutional Court's decision is related to the ad hoc nature inherent in the Constitutional Court. Compliance with ethical standards in the decision-making process in law enforcement agencies is a crucial element in maintaining the trust and reputation of state administration in the eyes of the public. The presence of ethical standards in the Constitutional Court is considered the basis for upholding constitutional principles which are moral and behavioral guidelines for all members of the judiciary.